Islamic Law Codification: The Friction on Authority of Islamic Law Establishment - Afdal, Windi (Faculty of Law, Universitas Negeri Semarang, 2016)
This paper is intended as a historical research study on renewal business through technical codification of Islamic law (Taqnin) as well as theoretical implications of the legislation (Tashri’) of Islamic law through the political authorities called parliament. The authors conclude that taqnin and tashri’ as an instrument of reform in Islamic Law is not something new from if analyzed from a historical perspective. This has been initiated in the past at least by Daulah Abbasiya in the Second Century Hijriyah or Eighth AD, but failed because of a conflict between the political authority (umara) and religion (ulama) in fighting authority of the establishment of Islamic law. This issue over and over again when codification movement and legislation of Islamic law in the modern era has theoretically implicated and it is a rare phenomenon that should be more deeply considering the renewal of Islamic law which is ongoing it contains at least one millennium old historical value.